Detection of circulating antigens for Taenia spp. in pigs slaughtered for consumption in Nairobi and surroundings, Kenya. (February 2019) - Akoko, James M.; MacLeod, Ewan; Thomas, Lian F.; Alarcon, Pablo; Kang'ethe, Erastus; Kivali, Velma; Muloi, Dishon; Muinde, Patrick; Murungi, Maurice K.; Gachoya, Julius M.; Fèvre, Eric M.
Abstract: Background & methods: Taenia solium a zoonotic tapeworm, responsible for neurocysticercosis in humans is a major public health threat, being a leading cause of acquired epilepsy in endemic regions. Eastern and southern African nations have experienced a recent rapid growth in pig production, including small-scale, free-range systems, with an accompanying increased risk of T. solium transmission. Seven hundred blood samples were collected from randomly selected pigs presented for slaughter at one of the largest porcine abattoir supplying unprocessed pork to Nairobi city and its surroundings. The samples were tested using an antigen ELISA to determine the prevalence of infection with Taenia spp. Results: The prevalence, adjusted for diagnostic test characteristics, was estimated to be 4.4% (95% CI: 1.9–7.1) with no significant statistical difference by pig sex or age. Infection with Taenia spp. was detected in pigs from all regions of the country supplying pigs to this slaughterhouse. Official post-mortem inspection did not detect cysticercosis in the duration of the study. Therefore, all the carcasses entered the food chains of Nairobi (70%), or neighboring counties (30%). Conclusions: Circulating antigens of Taenia spp. were detected in pigs slaughtered in one of the largest porcine slaughterhouses in Kenya, which receives pigs from several regions in the country. This is an indication that pigs entering the value chain are raised under poor husbandry conditions and that pork consumers in Nairobi and its surroundings may be exposed to the important zoonotic parasite. Whilst further research utilizing full carcass dissection is required to confirm T. solium positive cases, interventions to improve food-safety throughout the pork value chains in Kenya should be seriously considered. Highlights: Taenia spp. were detected in pigs (4.4%) slaughtered for Nairobi's pork market. Taenia spp. infections were present in pigs from each region in Kenya supplying pork to Nairobi during this study A comprehensive risk assessment is necessary to identify exposure to food-safety hazards in pork value chain Proper cooking of pork is recommended, as a way of reducing the risk of transmission of Taenia spp. to consumers Interventions to improve food-safety should consider the full pork value-chain